Law Enforcement on Campaign Prop Violations during the 2024 Election in Sidoarjo: Penegakan Hukum terhadap Pelanggaran Aturan Kampanye selama Pemilihan Umum 2024 di Sidoarjo - Sulaiman, Safia Adysti Mutiara Aaliyah; Phahlevy , Rifqy Ridlo (Indonesian Journal of Law and Economics Review, 2025)
General Background: The 2024 General Election in Indonesia emphasized transparency and fairness, with campaign periods becoming critical for political competition. Specific Background: In Sidoarjo Regency, numerous campaign prop (APK) violations occurred, reflecting challenges in compliance with electoral regulations. Knowledge Gap: Limited studies have analyzed empirical data on the scale and type of campaign prop violations at the regional level in relation to local law enforcement practices. Aims: This study examines the forms of campaign prop violations and law enforcement measures undertaken by the Sidoarjo Regency Election Supervisory Agency (Bawaslu) to ensure alignment with election law. Results: Findings indicate 5,599 total violations, dominated by the PDIP party with 1,068 cases, primarily related to the misuse of public facilities for campaign materials. Enforcement actions included administrative sanctions such as written warnings and prop removal. Novelty: This research provides region-specific empirical data on electoral violations and demonstrates the role of local Bawaslu in maintaining legal compliance. Implications: The study underscores the necessity of stricter administrative penalties and improved supervision to promote lawful and ethical campaigning practices. Highlights: PDIP recorded the highest number of campaign prop violations (1,068 cases). Most violations involved the misuse of public facilities and green spaces. Bawaslu’s enforcement aligns with the Election Law through structured administrative actions. Keywords: Campaign Props; Election Law; Sidoarjo; Bawaslu; Administrative Sanctions